Inequities in exposure to occupational risk factors between Māori and non-Māori workers in Aotearoa New Zealand. Issue 9 (2nd May 2018) - Denison, Hayley J; Eng, Amanda; Barnes, Lucy A; Cheng, Soo; 't Mannetje, Andrea; Haddock, Katharine; Douwes, Jeroen; Pearce, Neil; Ellison-Loschmann, Lis
Abstract : Background: Health inequities between indigenous and non-indigenous people are well documented. However, the contribution of differential exposure to risk factors in the occupational environment remains unclear. This study assessed differences in the prevalence of self-reported exposure to disease risk factors, including dust and chemicals, physical factors and organisational factors, between Māori and non-Māori workers in New Zealand. Methods: Potential participants were sampled from the New Zealand electoral rolls and invited to take part in a telephone interview, which included questions about current workplace exposures. Logistic regression, accounting for differences in age, socioeconomic status and occupational distribution between Māori and non-Māori, was used to assess differences in exposures. Results: In total, 2344 Māori and 2710 non-Māori participants were included in the analyses. Māori had greater exposure to occupational risk factors than non-Māori. For dust and chemical exposures, the main differences related to Māori working in occupations where these exposures are more common. However, even within the same job, Māori were more likely to be exposed to physical factors such as heavy lifting and loud noise, and organisational factors such as carrying out repetitive tasks and working to tight deadlines compared with non-Māori. Conclusions: This is one of the first studies internationally to compare occupational risk factors between indigenous and non-indigenous people. These findings suggest that the contribution of the occupational environment to health inequities between Māori and non-Māori has been underestimated and that work tasks may be unequally distributed according to ethnicity.